Optimalisasi Permainan Tradisional dalam Menstimulasi Holistik dalam Pendidikan Islam - Pamungkas, Eqviesta Runtun; Ichsan, Yazida; Yuliana, Vita; Albana, Rifaah Salwa; Saputra, Rasyid Herbanu Indra (Lembaga Yasin AlSys, 2022)
Optimizing traditional games in improving holistic Islamic education is an important concern. This study aims to determine the benefits of traditional games that are often played by children so that they can be maximized according to the needs that must be met. The research method used is by reviewing regularly and taking articles as references. The search results for related journals were obtained from various journals which were analyzed using data techniques related to the theme. Researchers also made observations of small children who were playing traditional games. The result of the research is that traditional games are very important to be preserved. Besides making the body healthy, traditional games help educate children, especially the physical aspects related to mental and psychological processes. This is important because a small child who is used to playing traditional games will form a character indirectly. Children in today's era are expected to be able to understand the meaning of a traditional game contained in it and be able to apply character values ​​in everyday life.